A REVIEW ON MEDIA RICHNESS AFFECTING PURCHASE INTENTION ON INSTAGRAM: THE MEDIATING ROLE OF BRAND LOYALTY - Hasim, Muhammad Asyraf; Shahrin, Muhammad; Wahid, Rosni Ab.; Shamsudin, Mohd Farid (International Journal of Psychosocial Rehabilitation, 2020)
Scant evidence is available on how social media richness influence brand loyalty and consumers’ purchase intention towards a product. Social media nowadays is among the best marketing platforms for an organisation to get in touch with potential and current customers. Instagram is one of social media platforms for people to interact socially. This new media platform wins the believe-in of customers by linking with them at a deeper level utilising the media richness it has. The blast of social media trend in business today is as amazing as that and the speed at which it is improving is frustrating. More organisations identified huge potential that social media has and started to use them with enhancements to power their marketing promotions. This study explores the relationship of media richness on Instagram towards consumers’ intention to purchase mediated by brand loyalty. A survey of 249 respondents in Malaysia who follow the same Instagram accounts offering similar products, this study develops a structural equation model that helps to address gaps in prior social media richness, brand loyalty, and purchase intention literatures. Partial least square structural equation modelling (PLS-SEM) applied to fit the data in the hypothesised model. The outcome of study is useful to both researchers and business practitioners to understand the importance of social media richness specifically utilising Instagram as business platform. Future study should consider on discovering different perspective of media richness involving other types of social media.